Learning Achievements on Handball Basic Skills through the Instructional Plan of Davie’s Practical Skill for Grade 6 Students at Anuban Maha Sarakham School - Sritowpakdee, Kumpang; Tongjunhard, Nittaya; Dechsri , Prapansak; Jatuchai, Sirinthon; Waengwan, Kanjana (Interdisciplinary Academic and Research Journal, 2023)
Promoting exercise and basic sports to become a way of life by encouraging children, youth, the general public to have a correct understanding of exercise, first aid, and some sports that are necessary for life skills. The objective of this research is to promote physical activity and basic sports as a way of life by enhancing correct knowledge and understanding of exercise, basic first aid, and the importance of certain sports skills for life skills. This research aims to: (1) Determine the effectiveness of the Davie’s learning management plan for developing basic skills in handball, based on the 75/75 standard criteria. (2) Compare the learning outcomes before and after using a test measuring basic handball skills. (3) Explore the satisfaction level of students towards the Davie’s teaching approach for developing basic handball skills. The sample group consists of 42 Grade 6/2 students from Anuban Maha Sarakham school in the academic year 2022. The research tools used in this study include the Davie’s learning management plan, a test measuring learning outcomes of basic handball skills, a satisfaction questionnaire regarding the Davie’s teaching approach, and statistical analysis tools such as mean, standard deviation, and t-test. The research findings revealed that: (1) The effectiveness of the Davie’s learning management plan for developing basic handball skills had a score of 85.90/78.17, which was higher than the set criteria of 75/75. (2) The learning outcomes after using the Davie’s teaching approach were significantly higher than before, with statistical significance at the .05 level. And (3) student satisfaction with learning management about basic handball skills using Davie’s practical skills teaching model overall was at the highest level.